2018
DOI: 10.1016/j.enpol.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

We choose what we like – Affect as a driver of electricity portfolio choice

Abstract: This page was generated automatically upon download from the ETH Zurich Research Collection. For more information please consult the Terms of use. ETH Library We choose what we like-Affect as a driver of electricity portfolio choice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Though the Swiss public does not exhibit uniform preferences with regard to the expansion of renewables domestically, a main difference appears to be in terms of how best to combine domestic renewable power productionwith either renewable imports or non-renewable technologies (Jobin & Siegrist, 2018). In this study, the demonstrated portfolio preferences were mainly driven by the participants' affective responses, that is, the feelings evoked by energy technologies.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Though the Swiss public does not exhibit uniform preferences with regard to the expansion of renewables domestically, a main difference appears to be in terms of how best to combine domestic renewable power productionwith either renewable imports or non-renewable technologies (Jobin & Siegrist, 2018). In this study, the demonstrated portfolio preferences were mainly driven by the participants' affective responses, that is, the feelings evoked by energy technologies.…”
Section: Introductionmentioning
confidence: 69%
“…In this study, the demonstrated portfolio preferences were mainly driven by the participants' affective responses, that is, the feelings evoked by energy technologies. In general, the more positive people's feelings about a given energy technology are, the more likely they are to include that technology in their portfolio (Jobin & Siegrist, 2018). Yet, appeals have been made that energy consumers, among others, should be more informed about their energy-related choices and rely on facts rather than opinions (Stern et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Past work with climate views included has found that believing that global warming is caused mostly by humans is significant for renewable energy support in some studies, but not in others [45,71,72], and that the public does consider emissions when weighing energy preferences [71]. Additionally, general environmental views have been found to influence energy preferences [4,5,10,73,74], though this is also not consistently measured across studies. Furthermore, environmental views and climate change beliefs may be more strongly related to support for fossil fuels-based energies than for renewable energies, which seem to be less polarizing overall.…”
Section: Public Opinion Research On Energy Preferencesmentioning
confidence: 99%
“…Many factors underlie energy policy decisions at state and federal levels, of which public opinion is one [1][2][3]. A growing body of social science literature examines public preferences for various energy sources [2,[4][5][6][7][8][9], but studies rarely measure public opinion on more than a few energy sources in the same survey effort (with some exceptions [2,10]), complicating a full picture of preferences across renewable and non-renewable options. They also rarely incorporate populations from more than one country.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, their preferences toward these sources are based on their views that wind is cleaner and less expensive than coal. Research has further demonstrated that this structure of public opinion toward energy—that is, that people’s attitudes are shaped by their perceptions of the energy resources’ attributes—extends to energy siting [15] and policy preferences [15, 39, 40, 41].…”
Section: Introductionmentioning
confidence: 99%